Fatores sociodemográficos e clínicos relacionados a adesão e acompanhamento do uso da profilaxia pós- exposição sexual para o HIV - Andrade, Ana Carla Cavalcanti de (2018)
Introduction: The dissemination of the Human Immunodeficiency Virus is still a public health problem, and in order to prevent it, the post-exposure prophylaxis for the virus stands out. Objective: To analyze the adherence and follow-up of the use of PostExposure Prophylaxis for Human Immunodeficiency Virus according to sociodemographic and clinical aspects. Methods: Descriptive study, quantitative, using secondary data sources, performed in a referral hospital in Paraíba, with a sample of 201 medical records of users who used the prophylaxis, August 2015 to December 2016. The data collected were recorded in form, typed in spreadsheet in Microsoft Office Excel 2003 and transported to the SPSS version 20.0 program, and analyzed using descriptive statistics, logistic regression model and multiple correspondence analysis. The study was approved by the Research Ethics Committee of the Health Sciences Center of the Federal University of Paraíba, under CAAE 65610617.9.0000.5188. Results: Of the 201 individuals seeking prophylaxis was featured male (80.1%), aged 15-29 years (53.7%), mulatto (76.1%), heterosexual (63.7), unmarried (80.1%), higher level of education (45.3%), diversified occupation (52.6%), geographic origin of the capital (79.6%) and the fact that exposure to non-use of the condom (73.1%). The users received the antiretroviral drugs at the first visit, but 118 (58.7%) did not return to the service and 83 (41.3%) partially attended the established consultations. The probability of non-adherence was higher in the age group of 15 to 29 years, of heterosexuals and users with average level of schooling. Conclusion: The fact that the patient did not attend the consultations for clinical-laboratory follow-up does not mean that he / she did not adhere to the prophylaxis, since the antiretroviral drugs are available to be taken at home. In this way, ensuring the clinical follow-up of the user becomes important for pharmacological adherence, through the monitoring of undesirable symptoms and evaluation of the difficulties that may compromise this adherence.